The Dickman impulsivity inventory: Validation and measurement invariance among Portuguese young adults - Pechorro, Pedro (2021)
The Dickman Impulsivity Inventory (DII) measures impulsive personality related to both negative and positive behaviors and characteristics. The main aim of the present study was to examine the psychometric properties of the DII among a Southern-European sample of Portuguese young adults. Our convenience sample (N = 429, M = 22.11 years, SD = 3.35, range = 18–42), composed of women (n = 237, M = 22.08 years, SD = 3.35, age range = 18–42) and men (n = 192, M = 22.14 years, SD = 3.34, range = 18–35), was collected from a university context. The two-factor latent structure of the DII composed of functional and dysfunctional impulsivity was supported, although three items had to be removed due to low standardized loadings, and strong cross-gender measurement invariance was established. Our analyses of the DII also provided evidence of criterion-related validity, known-groups validity, and internal consistency/reliability. Our findings support the use of the DII among Portuguese young adults.